Morphological evidence suggestive of a hierarchical mode of glial cell diversification and intrinsic developmental plasticity within the murine enteric nervous system - Lefèvre, Marie A.; Bourgeois, Mylène; Soret, Rodolphe; Pilon, Nicolas (Frontiers in Neuroscience, 2025)
Enteric glial cells represent a highly heterogeneous cell population residing both within and outside the ganglia and inter-ganglionic fiber bundles that form the core networks of the enteric nervous system (ENS). Despite the availability of several relevant single-cell transcriptomic datasets, the classification of enteric glia in various subtypes is still mainly based on their particular location and associated morphological attributes. We recently reported that these “topo-morphological” enteric glia subtypes gradually appear during early postnatal development in healthy wildtype mice, under the influence of structural tissue changes that occur during this period. This process is also influenced by the source of ENS progenitors, with notable biased contributions by Schwann cell precursors (SCPs). This prior work further suggested the existence of a hierarchical program of spatiotemporal differentiation, whereby intra-network enteric glia (i.e., within ganglia and fiber bundles) of the myenteric plexus sequentially give rise to nearby extra-network enteric glia as well as to more distant intra- and extra-network enteric glia of the submucosal plexus. To learn more about enteric glia diversification, we reasoned that the Nr2f1Spt/Spt mouse model of Waardenburg syndrome type IV could be particularly informative, as the absence of ENS in the colon of these mice is specifically due to premature glial differentiation of ENS progenitors before birth. Our new analyses of the ENS-containing ileum from these mice now also reveal abnormal acquisition of enteric glia diversity after birth. These alterations of enteric glia diversification are in agreement with the previously proposed hierarchical differentiation model in wildtype mice. This work also uncovered an intriguing neuronal phenotype in Nr2f1Spt/Spt mice in which a reduction in the number of neurons is associated with an increase in their size. Many of these larger neurons also co-express the glia marker S100β, which together with the noted increased contribution of SCPs to the overall pool of enteric glia further highlight the remarkable plasticity of the developing ENS.